2016
DOI: 10.1017/s0950268816000704
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal disease epidemiology in Australia 10 years after implementation of a national conjugate meningococcal C immunization programme

Abstract: Australia implemented conjugate meningococcal C immunization in 2003 with a single scheduled dose at age 12 months and catch-up for individuals aged 2-19 years. Several countries have recently added one or more booster doses to their programmes to maintain disease control. Australian disease surveillance and vaccine coverage data were used to assess longer term vaccine coverage and impact on invasive serogroup C disease incidence and mortality, and review vaccine failures. Coverage was 93% in 1-year-olds and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Since the meningococcal C conjugate vaccines (MenCCV) were added to the National Immunisation Program in 2003, the incidence of group C meningococcal disease in Australia has remained very low among both vaccinated and unvaccinated people. This finding of indirect protection (herd immunity) is consistent with observations of reduced carriage prevalence among vaccinated adolescents in the United Kingdom 7 , 8 . The recent development of two MenB vaccines that afford protection against multiple strains provides new opportunities for preventing group B disease.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Since the meningococcal C conjugate vaccines (MenCCV) were added to the National Immunisation Program in 2003, the incidence of group C meningococcal disease in Australia has remained very low among both vaccinated and unvaccinated people. This finding of indirect protection (herd immunity) is consistent with observations of reduced carriage prevalence among vaccinated adolescents in the United Kingdom 7 , 8 . The recent development of two MenB vaccines that afford protection against multiple strains provides new opportunities for preventing group B disease.…”
supporting
confidence: 86%
“…First, the peak incidence of MenC disease was in late adolescence, rather than in infancy and early childhood; second, case fatality rates for adolescent patients were higher for MenC disease; third, there was no disparity between Indigenous Australians and others in the incidence of MenC 17 . This epidemiological profile led to selecting the schedule of a single dose of MenCCV at age 12 months or later (initial or catch‐up doses); together with an extensive catch‐up campaign for children and adolescents, this markedly reduced MenC incidence to its current low levels through a combination of direct and indirect (herd immunity) effects 7 , 8 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…The meningococcal C deaths in our study occurred between 2005 and 2007, with most children eligible for meningococcal C vaccine catch‐up programmes under the NIP. Although meningococcal C vaccination coverage has been high (93%), coverage is lower in catch‐up cohorts (70%) . Most meningococcal deaths in our study were due to meningococcal B disease; most occurred before the meningococcal B vaccine (which is now recommended but not funded under the NIP for young children, particularly those aged <24 months, adolescents aged 15–19 years and those with specific medical conditions) became available in 2014.…”
Section: Discussionmentioning
confidence: 70%
“…We identified 12 deaths due to meningococcal disease over the 10‐year study period, substantially less than the 26 deaths identified in NSW in children less than 15 years between 2000 and 2007 . There has been a dramatic decline in meningococcal C disease since the introduction of the meningococcal C immunisation programme in 2003 . The meningococcal C deaths in our study occurred between 2005 and 2007, with most children eligible for meningococcal C vaccine catch‐up programmes under the NIP.…”
Section: Discussionmentioning
confidence: 79%
“…Craig et al. reported a lower prevalence of SBIs (7.2%) and IBIs (0.4%) from data collected between 2004 and 2006, which could be explained by the high level of vaccine coverage and herd immunity in Australia . However, despite suboptimal vaccination coverage in France, IBIs have decreased in recent years following steady advances in the pneumococcal conjugate and the decrease in group C invasive meningococcal disease .…”
Section: Discussionmentioning
confidence: 99%